Rare Co-occurrence of Beta-Thalassemia and Pseudoxanthoma elasticum: Novel Biomolecular Findings - Boraldi, Federica; Lofaro, Francesco Demetrio; Costa, Sonia; Moscarelli, Pasquale; Quaglino, Daniela (Frontiers in Medicine, 2020)
A number of beta-thalassemia patients, independently from the type of beta-thalassemia (β0 or β+) and blood transfusion requirements, may develop, after puberty, dermal, cardiovascular and ocular complications associated with an ectopic mineralization phenotype similar to that observed in another rare genetic disorder, namely Pseudoxanthoma elasticum (PXE). To data, the causes of these alterations in beta-thalassemia patients are not known, but it has been suggested that they could be the consequence of oxidative stress-driven epigenetic regulatory mechanisms producing an ABCC6 down-regulation. Since, in the last years, several genes have been associated to the ectopic mineralization phenotype, this study, for the first time, applied, on beta-thalassemia patients with ectopic mineralization phenotype, a genetic testing strategy using a multigene panel. Gene selection was done on the basis of: i) their genetic involvement in calcification diseases or ii) their role in calcium-phosphate equilibrium. Data demonstrate the co-occurrence of beta-thalassemia and PXE and, in addition to pathogenic variants, functional polymorphisms may further influence connective tissue manifestations. The use of a multigene panel-based next generation sequencing represents a useful time- and cost-effective approach, allowing to identify sequence variants that might improve prognostic assessment and better management of these patients, especially in the current era of precision medicine aiming to identify individual optimal care based on a unique personal profile.